Local Delivery of Platelets with Encapsulated lloprost to Balloon Injured Pig Carotid Arteries: Effect on Platelet Deposition and Neointima Formation - Banning, Adrian; Brewer, Lesley; Wendt, Maria; Groves, Peter H; Cheadle, Hilary; Penny, William J; Crawford, Neville (Thrombosis and Haemostasis, 1997)
Local delivery of a drug to the arterial wall during angioplasty is an approach which might reduce the incidence of occlusive events such as thrombosis and restenosis, without the risk of systemic side effects. By exploiting their natural primary haemostatic properties, platelets, with encapsulated drugs, can be targeted to a vessel wall injury site and act as a depot for sustained release. The platelet plasma membrane can be reversibly permeabilised by high voltage, short duration electrical pulses (electroporation). Drugs will diffuse into porated platelets and become trapped on resealing. We have studied the effects of autologous platelets, electroloaded with the stable prostacyclin analogue, iloprost, on platelet deposition and neointima formation in a pig carotid angioplasty model. Iloprost loaded or control platelets were delivered locally and immediately to the balloon injured site using a double balloon delivery catheter. Acute platelet deposition was measured using 111-Indium, and neointima formation at 21 days post angioplasty was assessed by morphometric analysis. In pigs treated with iloprost loaded platelets, platelet deposition on the artery at 2 hours post injury was dramatically reduced (to approximately monolayer coverage), when compared with arteries from pigs treated with control platelets. In pigs with deeply injured arteries, i.e. with extensively ruptured internal elastic lamina (IEL), platelet deposition was reduced by 88% compared with control arteries (118 ± 20 X 106/cm vs. 14 ± 2 X 106/cm, means ± SE, 2P <0.001). In minimally injured arteries (IEL intact) a 65% reduction in platelet deposition was observed (55 ± 24 X 106/cm vs. 19 ± 3X 106/cm, 2P <0.002). A high concentration of free iloprost, delivered to the angioplasty site, with control platelets, had far less effect on platelet deposition, substantiating the advantage of platelet encapsulation. At 21 days post injury, morphometry of the carotid arteries after treatment with iloprost loaded platelets showed significant reductions in intimal area and intimal/medial ratios in minimally injured vessels (P <0.05) as compared with vessels from pigs treated with control platelets. With deeply injured vessels, the mean differences (control vs. treated) for the same morphometric parameters were not significant.This novel approach of electro-encapsulating drugs within autologous platelets, and using them as highly biocompatible and biodegradable drug targeting vehicles might, with the appropriate choice of encapsulated agent, have potential for reducing the incidence of occlusion after angioplasty and thrombolysis procedures.